PENGGUNAAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN KEMAMPUAN PESERTA DIDIK PADA MATA PELAJARAN IPS MATERI KEBERAGAMAN BUDAYA - Yanti Laelasari, Yeni Sulaeman, Rifki Arif Nugraha, Omah Mukarromah (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
This research is motivated by the lack of social science learning which is not going well, this can be seen from every lesson because the teacher only uses conventional methods such as lectures. As a result, students are not enthusiastic and tend to be passive because the learning process is monotonous and boring. As a result, teachers dominate the class more than students. Therefore, to make lessons easier for students to understand, teachers need learning media that can support student learning in social science (IPS) lessons, resources or tools. The aim of this research is to find out how the use of animated videos as learning media can improving student learning outcomes in class IV social science (IPS) subjects at Saruni 3 Pandeglang Elementary School. This research uses the method used, namely classroom action research (PTK). The results of this research show that there is a significant difference in student learning outcomes using the animated video learning method, as indicated by the results of the independent sample test in pre-graduate with an average score of 53.1, with a completion percentage of 25%, cycle 1 stage got a score an average of 72.39 with a completeness percentage of 32% in the second cycle stage there is an average value of 76.55 with a completeness percentage of 71% and in the third cycle stage there is an average value of 82 with a completeness percentage of 86% therefore, it can be seen conclude that the use of animated video learning media has a positive effect on students' learning success in social science (IPS) subjects on cultural diversity in class IV in Negeri Saruni 3, Majasari Pandeglang